THE INFLUENCE OF PRICE AND SHOPPING CONVENIENCE ON ONLINE PURCHASE DECISIONS OF STUDENTS OF THE FACULTY OF COMPUTER SCIENCE, SANTO THOMAS CATHOLIC UNIVERSITY ON THE E-COMMERCE SHOPPE - Bangun, Yohana; Gultom, Parapat (Jurnal Manajemen dan Bisnis, 2024)
In the current era of globalization, the internet is increasingly sophisticated and continues to develop, especially in the field of marketing, both in national and international markets. This competition is coupled with selectiveness. Companies must be able to communicate their products to consumers in selecting products for consumption. Under conditions like this, companies must be responsive to consumer desires. One of the popular e-commerce sites in Indonesia is Shopee.co.id. In this research, the independent variables are price (X1) and convenience (X2), while the dependent variable is the online purchasing decision (Y). This research aims to determine and analyze the influence of price and shopping convenience on online purchasing decisions of students from the Faculty of Computer Science at the E-Commerce Shoppe. The type of research used is quantitative research. The data processed is the result of distributing questionnaires to students of the Faculty of Computer Science at events using Google Form. The number of samples that will be used is 86 students. The sampling technique is: accidental sampling. In analyzing the data, the instruments used are the validity test, reliability test, multiple linear regression equation, f test, t test, and coefficient of determination test. The results of this research show that the results of the multiple linear test show that price has a negative and significant effect , comfort has a positive and significant effect. significant to online purchasing decisions of St. Catholic University Computer Science students. Thomas at E-Commerce Shoppe purchasing decisions.